Balancing efficiency and sustainability in waste collection fleet operations: A fleet optimization and electrification perspective in a real case study - M. Ghoreishi; F. Santori; L. Carloni; M. Cresta; A. Geri; T. Bragatto (Cleaner Engineering and Technology)
The optimization of municipal solid waste collection presents a dual challenge of improving operational efficiency while minimizing environmental impact. This study addresses these challenges by developing an optimized distribution plan incorporating sustainable development principles within a capacitated vehicle routing problem framework. This research addresses the gap in evaluating the operational cost and environmental impacts of MSW management, particularly focusing on optimizing fleet electrification and waste collection processes. This study aims to fill this gap by proposing an optimization model for waste collection, integrating fleet electrification to reduce greenhouse gas emissions and operational costs. In addition, the optimized fleet routes are utilized in this study to evaluate five electrification scenarios (20%–100% electrification) to analyze economic and environmental impacts using MATLAB. This research focuses on a case study in Narni, Italy, where ASM Terni S.p.A. manages waste collection operations as a multi-utility in Italy. Electrification scenarios show significant reductions in fuel costs and emissions, even exploiting a decision support system that optimally manage charging sessions of the Electric Vehicles after the daily waste collection using available Charging Stations in the headquarters.